CRISPR/Cas9‐based genome engineering: A new breakthrough in the genetic manipulation of filamentous fungi. (29th November 2020) - Ullah, Mati; Xia, Lin; Xie, Shangxian; Sun, Su
Abstract: Filamentous fungi have several industrial, environmental, and medical applications. However, they are rarely utilized owing to the limited availability of full‐genome sequences and genetic manipulation tools. Since the recent discovery of the full‐genome sequences for certain industrially important filamentous fungi, CRISPR/Cas9 technology has drawn attention for the efficient development of engineered strains of filamentous fungi. CRISPR/Cas9 genome editing has been successfully applied to diverse filamentous fungi. In this review, we briefly discuss the use of common genetic transformation techniques as well as CRISPR/Cas9‐based systems in filamentous fungi. Furthermore, we describe potential limitations and challenges in the practical application of genome engineering of filamentous fungi. Finally, we provide suggestions and highlight future research prospects in the area. Abstract : CRISPR/Cas9: its impact on the study of filamentous fungi